2022
DOI: 10.1186/s13195-022-01067-8
|View full text |Cite
|
Sign up to set email alerts
|

Predicting conversion of brain β-amyloid positivity in amyloid-negative individuals

Abstract: Background Cortical deposition of β-amyloid (Aβ) plaque is one of the main hallmarks of Alzheimer’s disease (AD). While Aβ positivity has been the main concern so far, predicting whether Aβ (−) individuals will convert to Aβ (+) has become crucial in clinical and research aspects. In this study, we aimed to develop a classifier that predicts the conversion from Aβ (−) to Aβ (+) using artificial intelligence. Methods Data were obtained from the Alzh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…Similarly, another study by the same group 39 , detected baseline Aβ-positivity using demographic, APOE, and cognitive information and achieved an AUC of 0.65 in cognitively healthy individuals. However, we are aware of only two studies that have focused on predicting future Aβ-positivity 12,44 . The first study by Elman et al 44 examined the association of baseline cognitive measures with progression to Aβ-positivity in Aβ-negative individuals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, another study by the same group 39 , detected baseline Aβ-positivity using demographic, APOE, and cognitive information and achieved an AUC of 0.65 in cognitively healthy individuals. However, we are aware of only two studies that have focused on predicting future Aβ-positivity 12,44 . The first study by Elman et al 44 examined the association of baseline cognitive measures with progression to Aβ-positivity in Aβ-negative individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The first study by Elman et al 44 examined the association of baseline cognitive measures with progression to Aβ-positivity in Aβ-negative individuals. The second study conducted by Park et al 12 employed machine learning algorithms to predict future Aβ-positivity in Aβ-negative individuals. In Park et al 12 study, they used a PET biomarker for subject classification in Aβ+/Aβ-groups and developed a classifier with baseline age, gender, APOE4 genotype, and PET SUVR measures in ADNI data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, lecanemab, a humanized IgG1 monoclonal antibody that targets soluble aggregated Aβ species (protofibrils), demonstrated robust amyloid-PET reduction in early AD [50]. One recent study developed a DL model to predict amyloid-PET positivity conversion, which might contribute to the screening of early treatment candidates [54] as it has been reported that positivity in both amyloid and tau PET scans put cognitively unimpaired individual at high risk for future cognitive decline [55 ▪▪ ]. In clinical settings, large multicentre studies have shown that amyloid-PET results change both diagnosis and patient management and that quantification can accurately predict rates of cognitive decline.…”
Section: Amyloid-petmentioning
confidence: 99%